Active Antibiotics Production by Actinomycetes Indigenous To Saudi Arabia Soils: Life Sciences-Microbiology For Health Care - Fetoon M. Alkhelaiwi; Ismet Ara; Nadine Moubayed (International Journal of Life Science and Pharma Research, 2022)
Streptomyces are the most popular among the Actinomycetes groups and found in soils worldwide. They form an important part of the soil ecology within the Actinomycetales order. Streptomyces are diverse as secondary antibiotic metabolites such as Novobiocin, Amphotericin, Vancomycin, Neomycin, Gentamicin, Chloramphenicol, Tetracycline, Erythromycin and Nystatin. Thus, the current study was aimed to isolate, identify and assess the active antibiotic metabolites produced by different actinomyces sp. found in Saudi Arabian soils. Six samples were collected from desert soils of the Al Thumamah area and analyzed using GS-MS. Scanning Electron Microscopy was used to identify the bacterial strains along with their antibiotic metabolites effectiveness of secondary metabolites (antibiotics) against different Gram-positive (Bacillus subtilis, Staphylococcus aureus), negative pathogens (Pseudomonas aeruginosa, Escherichia coli, Salmonella suis, and Shigella sonnei) as well as the fungal strain Candida albicans was investigated. Thirty active bacterial (F1-30) strains were isolated from the soil samples and the strains F3, F7, F22, F30 have white, gray, pink, yellow and red colours respectively. Only ten strains (F13, F14, F15, F16, FI7, F18, F19, F20, F21, and F22) were found to have antimicrobial activity against at least one pathogen. The optimum growth environment was pH 4-10, temperature (300C), and NaCl (7% w/v) concentration. According to our findings, the extreme desert environment of Al Thumamah from Saudi Arabia is rich in its actinobacterial population with diverse colouring groups and various physiological and biochemical properties. This shows it’s capability of generating secondary metabolite elements that could inhibit pathogenic microorganisms.